Ascorbic acid and calcium uptake in pineapple tissue through different sucrose concentrations of impregnation solution - Fernández, Paula Rosana (2019)
Fil: Fernández, Paula Rosana. Universidad Nacional de Misiones. Instituto de Materiales de Misiones; Argentina.